Occurrence of the calanoid copepod Acartia (Odontacartia) ohtsukai in Laizhou Bay, the Bohai Sea, China, and its relationship with environmental factors - Zuo, Tao; Wang, Di; Li, Yongtao; Niu, Mingxiang; Cheng, Zhaolong; Wang, Jun (Frontiers in Marine Science, 2024)
In this study, we examined the short-term variation in the abundance of copepod Acartia specimens, identified previously as Acartia pacifica, in Laizhou Bay, an estuarine bay in the southern Bohai Sea in northern China. Monthly samples were collected from May 2011 to April 2012, excluding December 2011 and January to February 2012 due to ice. Based on its morphological characteristics, Acartia ohtsukai was distinguishable from A. pacifica for the first time in the Laizhou Bay. A. ohtsukai was sporadically present from summer to autumn, with the highest abundance and occurrence in September. It appeared in June when the water temperature was above 20°C, and disappeared in November when the water temperature decreased to less than 10°C. During the surveyed months, A. ohtsukai was more commonly found inshore with salinity less than 28 than offshore in the bay. Correlation analysis revealed that temperature and chlorophyll a concentration significantly influenced the monthly variations in A. ohtsukai abundance. We also compared the occurrence of A. ohtsukai with that of three species from the genus Tortanus (Tortanus derjugini, Tortanusforcipatus, and Tortanusspinicaudatus) in the Laizhou Bay. The coexistence of A. ohtsukai and T. derjugini in the bay suggests that their ecological habitats are similar to those of brackish-water species.